Millennium development goal of improving maternal health Bangladesh: a review of concepts - Akhter, Sanzida (BRAC University, 2010)
Bangladesh is one of the signatories to the Millennium Declaration 2000, of which, improving maternal health is one of eight goals. Along with the global targets of reducing maternal mortality rate by three quarters between 1990 and 2015, Bangladesh has set some additional targets for achieving the goal by 2015. The main objective of this paper is to make an extensive review on selected studies on maternal mortality, with particular reference to: (1) historical and present interventions to avert maternal mortality, and (2) the six targets of MDG Five set for Bangladesh. A conceptual framework has been developed where the global target is integrated into the targets set by Bangladesh. This paper concludes maternal mortality is a multifaceted and broad based issue to be considered. The inclusion of additional targets in MDG Five for Bangladesh also reflects this complex reality of maternal mortality.